2022
DOI: 10.1177/20494637221133630
|View full text |Cite
|
Sign up to set email alerts
|

Compassion focused therapy for pain management: ‘3 systems approach’ to understanding why striving and self-criticism are key psychological barriers to regulating activity and improving self-care for people living with persistent pain

Abstract: Background This paper describes the development of an eight-week Compassion Focused Therapy for Pain Management (CFT-PM) group. This group was specifically designed for ‘strivers’ a sub-group of people with persistent pain who tend to engage in over-activity and resist making reasonable adjustments to their activity levels to accommodate their persistent pain. ‘Strivers’ tend to cope by ignoring their pain and pushing on through, in the shorter term leading to ‘boom and bust’ activity-related exacerbations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Similar outcomes were obtained in another meta-analysis with a systematic review: individualised physiotherapeutic interventions were shown to have a modest yet significant effect on pain reduction, with pain relief being more effective when combined with CBT (Fleckenstein et al, 2022). Some studies have analysed the effects of third-wave therapies on reducing the severity of chronic pain (Barrett et al, 2021;Ma et al, 2023;Malpus et al, 2023;Norman-Nott et al, 2023). The results indicate pain relief, improved acceptance of the experience of pain and its associated limitations, and greater flexibility in managing discomfort.…”
Section: Spinal Pain Syndromesupporting
confidence: 61%
“…Similar outcomes were obtained in another meta-analysis with a systematic review: individualised physiotherapeutic interventions were shown to have a modest yet significant effect on pain reduction, with pain relief being more effective when combined with CBT (Fleckenstein et al, 2022). Some studies have analysed the effects of third-wave therapies on reducing the severity of chronic pain (Barrett et al, 2021;Ma et al, 2023;Malpus et al, 2023;Norman-Nott et al, 2023). The results indicate pain relief, improved acceptance of the experience of pain and its associated limitations, and greater flexibility in managing discomfort.…”
Section: Spinal Pain Syndromesupporting
confidence: 61%
“…However, it is notable that, while significant, the magnitude of improvement was small. For comparison, a recent study reporting outcomes from an 8-week pain management treatment based on compassion-focused therapy reported a significant improvement in self-compassion with a large effect ( Malpus et al, 2023 ). That study specifically selected treatment participants who displayed a pattern of “striving,” such that they tended to push through activities or use activities to distract from pain resulting in a “boom and bust” pattern ( Malpus et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, a recent study reporting outcomes from an 8-week pain management treatment based on compassion-focused therapy reported a significant improvement in self-compassion with a large effect ( Malpus et al, 2023 ). That study specifically selected treatment participants who displayed a pattern of “striving,” such that they tended to push through activities or use activities to distract from pain resulting in a “boom and bust” pattern ( Malpus et al, 2023 ). Additionally, there can be many barriers to engaging in self-compassion, such as fears that doing so may lower personal standards or lead to failure, and beliefs that one might not be deserving of self-compassion ( Gilbert et al, 2011 ; Carvalho et al, 2021 ; Biskas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is research exploring the effects of self-compassion interventions for chronic pain. For example, Compassion Focused Therapy (CFT) increased self-compassion and reduced pain disability in a sample of adults with chronic pain who engage in over-activity (Malpus et al, 2023). Another randomized controlled trial found that Mindful Self-Compassion training (MSC) reduced pain interference to a greater extent than Cognitive Behavioral Therapy (CBT) in chronic pain patients (Torrijos-Zarcero et al, 2021).…”
Section: Discussionmentioning
confidence: 99%